The Development Role Played by Targeted Development Investments in South Africa and Their Risk-Adjusted Performance Over a 10-Year Period - Gaqa, Nandipa (Graduate School of Business (GSB), 2021)
The study evaluated the development role of targeted development investments in South Africa and their risk adjusted performance over a 10-Year period, that is from 2008 to 2017. Targeted development investments as a subset of socially responsible investments have transformed the way capital is allocated towards development funding needs. In the South African context this study is relevant given it offers a contrast between investments made in the public sector where development impact is a key objective, versus private sector targeted investments that aim to achieve financial returns whilst also driving development impact objectives aligned to sustainable development goals. The role and impact of these investments in the post democratic era is put in the spotlight given the country is dealing with economic, social, and environmental challenges that have necessitated the need to assess the nature and role of the investment industry in solving these complex development challenges (Giampocaro & Pretorius, 2012). The study on the role of the public sector focused on the investments and development impact indicators tracked by the Top 3 public sector investment institutions or corporations. The analysis on the performance of the private sector TDI funds examined their risk adjusted performance using Treynor, Sharpe, Sortino, and Information ratios. The risk adjusted performance was used to test whether the TDI fund returns under or outperformed against five benchmark categories. The research findings showed mixed results where TDI funds either underperformed or outperformed against the benchmark categories. The findings highlighted the need for a hybrid development model where both the public and private sector actively play a role in the development landscape as guided by their respective investment mandates. The findings advocate for corporate and institutional investors to increase capital allocations and investments towards financing development needs given the scope to maximise investor returns, whilst considering socially responsible investing and issues relating to the development and empowerment of previously disadvantaged communities.